Identification of the Ergonomic Properties of Outdoor Fitness Chest Press Leg press and Pull Chairs Machines with Respect to the Anthropometric Characteristics of Iranian Women - Sanchooli, Zari; Sokhanguei, Yahya; Fatahi, Ali; Tabatabai Ghomsheh, Farhad (Journal of Clinical Physiotherapy Research, 2021)
Introduction: Appropriateness of ergonomic properties of outdoor fitness equipment with respect to anthropometric features of their users can reduce risk of injuries. The aim of this study was to investigate the appropriateness of the ergonomic indices of outdoor leg presses, chest presses, and pull chair machines with respect to anthropometric parameters in Iranian female athlete users. Material and Methods: 124 Iranian female athletes who used outdoor fitness machines in Iran were recruited. An engineering tape measure and an anthropometric kit were used to measure the dimensions of the chest press, leg press, pull chair machines and also anthropometry of female users. Next, using the anthropometric data and the fitness device standards based on trigonometric calculations, standard anthropometric computational dimensions of devices were obtained. Standard indices of outdoor fitness devices based on athlete’s anthropometric data were compared with the dimensions of outdoor fitness machines. A one-sample t-test was conducted on the collected data using SPSS software, version 21. Results: Comparison among all calculated ergonomic indices of leg press, chest press, and pull chair machines according to anthropometric features of female users and certain measured indices showed a significant difference (P<0.05), with exception of ergonomic variable of optimal horizontal distance from the back of seat pad to foot plate tip in the leg press machine (P=0.68). According to this significant difference, these devices were not ergonomic in terms of female athletes’ anthropometry. Conclusion: Based on the findings, ergonomic properties of leg press, chest press, and pull chair outdoor fitness machines did not meet the anthropometric variations in Iranian female users. Given this mismatch could play an important role in the occurrence of musculoskeletal injuries among female users of these devices, this study highlight the necessity of following ergonomic standards in the design and production of fitness equipment.